Thermal and entropy behavior of sustainable solar energy in water solar collectors due to non-Newtonian power-law hybrid nanofluids - Mabrouk, S. M.; Mahmoud, Tarek A.; Kabeel, A. E.; Rashed, A. S.; Essa, Fadl A. (Frontiers in Energy Research, 2023)
Introduction: Nanofluids, hybrid nanofluid possesses thermophysical features that boost the fluid performance. This research work is motivated by the utilization of water solar collectors that incorporate non-Newtonian, power-law hybrid nanofluid in a three-dimensional model, considering the two-phase model. Method: The primary objective of this study is to transform the governing equations of the flow model into a set of ordinary differential equations by employing the three-parameters group technique. Based on the innovative discoveries, two models incorporating new associated functions have been successfully developed for two distinct scenarios characterized by the power-law index, n. The impact of physical factors on the velocity profile, temperature distribution, concentration field, and entropy output of the system is clearly illustrated through a variety of graphs. Results: The results indicated that the inclination angle of 20° had the best thermal characteristics compared to other inclinations. The entropy generation reached its maximum value at temperature difference of 13 K due to irreversibility of the system, which indicates that the system is more efficient. Discussion: Furthermore, the increasing percentage in Nusselt number is predicted to be 28.18% when the Prandtl number is taken a range. The Sherwood number enhanced up to 18.61% with a range of Brownian motion. A quantitative comparison is conducted between the present results and the literature in order to validate the superior efficiency of the used method.